Ranking the quality of life indexes by years in Asian countries using multi-criteria decision-making methods - Celebi Demirarslan, Pinar; Akansel, Ilkben; Sonmez Cakir, Fatma (Asia-Pacific Journal of Regional Science, 2024)
The objective weighting methods recently introduced in the literature include method based on the removal effects of criteria (MEREC), logarithmic percentage change-driven objective weighting (LOPCOW), and modified preference selection index method (MPSI). The aim of this study was to analyze the effects of the above methods on criteria weights and rank in decision problems involving over 20 alternatives. Based on the quality of life index (QLI), the ranking of Asian countries was carried out by combining the above weighting methods with the multi-attributive ideal-real comparative analysis (MAIRCA). Combination of these methods has not been used before in this research area. Capitals of Asian countries were selected and evaluated with eight different criteria. MEREC, LOPCOW, and MPSI methods were used to weight the criteria. The MAIRCA method was used to rank the alternatives. These results were compared with Numbeo rankings. The MPSI method showed the closest ranking to the Numbeo ranking, exhibiting the highest Spearman rank correlation and lowest Euclidean distance. Given its straightforward applicability, the MPSI method is preferred among the aforementioned objective weighting methods, followed by the MEREC and then the LOPCOW methods. In addition, we also examined the applicability of the preference selection index (PSI) method to the data sets. The results indicate the PSI method may not calculate the criteria weights in decision-making problems where the number of alternatives is high.
Keywords: LOPCOW; MAIRCA; MCDM; MEREC; MPSI; Quality of Life Index